Էջեր Հ. Տեր–Աստվածատրյանցի «Աղէտների յուշագիրը» նորահայտ օրագրից (1918 թ.) - Մուրադյան, Սամվել («Զանգակ - 97»)
The consisting of 243 standard pages handwritten diary reflects the rnost important political, economical and ethnic incidents in the first half of 1918 in Transcaucasus, Turkey and other neighbouring countries. The author is well informed inhabitant of Tbilisi H.Astvatsatryants, who often participated in those incidents. The work has been kept in archivc of M.G.Nersisyan. In this publication the inscriptions made from 1st to 6th of March, 1918 are being presented to reader.
Keywords: Քաղաքականություն; Պատմություն; Մատենագիտություն